EMOTION ENGINEERING THROUGH DICTION AND IMAGERY IN THE LYRICS OF THE SONG "TERJERAT" BY KEY RAN PSYCHOLINGUISTIC LITERARY STUDY - Ratu, Ari; Rotty, Viktoty N.J; Ratu, Donal M. (Journal of Learning on History and Social Sciences, 2024)
The objectives of this research are 1. How can the language and images contained in the lyrics of the song "Terjerat" by Key Ran influence and stimulate the listener's emotions? 2. Are there differences in emotional interpretation between listeners with different cultural backgrounds regarding the lyrics of the song "Terjerat"? 3. How does the application of linguistic and literary techniques in the lyrics of the song "Terjet" help create a deep atmosphere and support emotional engineering? The method used in this research is a qualitative descriptive method. The approach that researchers will use to analyze the Engineering of Emotions through Language and Imagery in the lyrics of the song "Terjerat" by Key Ran is a textual analysis approach using Harold Bloom's theory (1930) to analyze song lyrics in depth to identify the language and image elements used to convey emotional messages to listeners. Apart from that, researchers used the mental image theory put forward by George Lakoff and Mark Johnson, to analyze the images created by the lyrics that influence the way you hear, understand and feel the song. The subject of this research is the lyrics of the song "Terjerat" by Key Ran. To collect data the technique used is technique. 1. Text analysis 2. Interviews with singers/composers 3. Literature study 4. Listener survey. The research results show: 1. The language and images contained in the lyrics of the song "Terjerat" can influence and stimulate the listener's emotions based on psychoanalytic engineering analysis, namely: word selection, visual imagery, repetition, grammar and rhythm, language style and metaphor, general themes, and Duality of Emotions 2. Listeners' interpretation after hearing this song is an interpretation based on the meaning of the song's lyrics 3. There is the application of linguistic and literary techniques in the lyrics of the song "Terjerat" which helps create a deep atmosphere and supports emotional engineering as seen from: Listener's emotional understanding, Connection with listeners, Message and meaning of songs, Creativity in the influence of emotions, Psychological Considerations in the Music Industry, Education and Language Arts.